Prevalence, awareness, treatment and control of hypertension in a rural community of Salem, Tamil Nadu - Kumar, K. Sathish; Chellavel Ganapathi, K.; Duraimurugan, M.; Selavaraj, R.; Kokila, K.; Megala, M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension, a global public health issue, is a major risk factor for NCDs like stroke, cardiovascular disease and chronic kidney disease. If Hypertension is detected early it is possible to minimize the risk of cardiovascular diseases, stroke and kidney failure. Objectives: To determine the prevalence of hypertension among the age group of >18 years in a rural community of Salem iii. To determine the association between hypertension and selected variables like age, sex, tobacco intake, alcohol intake, physical activity, Body mass index (BMI) and waist hip ratio iv. To assess the level of awareness, treatment and control of hypertension Methods: A Cross-sectional study was done in a rural community of Salem, Tamil Nadu during March-December 2016 among individuals aged ≥18 years. The final calculated sample size was 256. Convenience sampling method was used. Participants were interviewed using a structured interview schedule, their BP was measured and anthropometric measurements were taken. Hypertension was defined according to JNC VIII criteria. Data entry and analysis was done using IBM SPSS version-21 software. Results: Out of the 442 eligible persons approached 420 persons consented to participate. Prevalence of hypertension was 34%. About 16% of the respondents had never measured their BP in their life time. Increase in age, male gender, increase in BMI levels, tobacco and alcohol were found to be significant independent predictors of hypertension. Awareness, treatment and control of hypertension were found to be 31%, 23.2% and 11.2% respectively. Conclusions: Prevalence of hypertension was high but awareness was poor. It is recommended to advice the community about the risk factors of hypertension and regular BP check-up should be done among the community for early detection of hypertension and also for preventing complications.